2015
DOI: 10.1016/j.ygyno.2015.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology in ovarian carcinoma: Lessons from autopsy

Abstract: OBJECTIVE We challenge epidemiologic knowledge regarding ovarian carcinoma (OC) by bridging the gap between clinical and autopsy data. METHODS Autopsy reports, histological slides and clinical files from 660 patients in whom OC was diagnosed from 1975-2005 were studied (autopsy cohort, n=233; Clinical Cancer Registry from the local gyneco-oncologic center, n=427). RESULTS Out of the autopsy cohort, we identified four distinct subgroups of patients: 1) OC was diagnosed before autopsy, n=156 (67.0%). 2) OC was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…These studies demonstrated that, although EOC typically colonized a wide variety of organs and tissues, there was not one single metastatic site that was always involved by metastasis in all studied cases. The main site of metastasis was the peritoneum, including the parietal and visceral peritoneum and omentum, which was involved in 77% of cases on average among several reports (ranging between 53% and 99%, Table 1 ) [ 25 , 26 , 27 , 29 , 30 , 31 ]. Other commonly colonized sites identified by autopsy studies included lymph nodes (38–77% of cases), large and small intestine (44–86% of cases), liver parenchyma (45–59% of cases), and lung (33–39% of cases).…”
Section: Sites Of Eoc Metastasesmentioning
confidence: 99%
“…These studies demonstrated that, although EOC typically colonized a wide variety of organs and tissues, there was not one single metastatic site that was always involved by metastasis in all studied cases. The main site of metastasis was the peritoneum, including the parietal and visceral peritoneum and omentum, which was involved in 77% of cases on average among several reports (ranging between 53% and 99%, Table 1 ) [ 25 , 26 , 27 , 29 , 30 , 31 ]. Other commonly colonized sites identified by autopsy studies included lymph nodes (38–77% of cases), large and small intestine (44–86% of cases), liver parenchyma (45–59% of cases), and lung (33–39% of cases).…”
Section: Sites Of Eoc Metastasesmentioning
confidence: 99%
“…The most common and best known route of OC spread is the transcoelomic route. It is associated with metastasis within the peritoneal cavity and affects the surrounding peritoneal organs [ 4 , 5 ]. In this type of cancer, the dissemination of single cells, multicellular aggregates, and spheroids seed into the mesothelial layer and organs of the peritoneal cavity [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…EOCs are diagnosed predominantly at an advanced stage with widespread metastases throughout the peritoneal cavity (4)(5)(6). Manifestations of the disease are typically vague and do not become apparent until the disease is advanced and difficult to treat.…”
Section: Introductionmentioning
confidence: 99%